Classroom Wall Optimization Program to Enhance Creativity in Early Childhood at PAUD Nusa Indah - Yusuff, Adisti Ananda; Widyastuti, Putri Anggraeni; Rochyat, Indra Gunara; Khasanah, Nurul (Unram Journal of Community Service, 2025)
PAUD BKB Nusa Indah 04 is one of two early childhood education institutions located in Duri Kepa sub-district, West Jakarta. Currently, the number of students enrolled in early childhood education is around 20, divided into 2 classes: Kindergarten A and Kindergarten B. The school shares a building used for other activities such as posyandu. This makes the room conditions in this early childhood education center need to be adaptable to the activities being carried out.The situation analysis was conducted in stages. First, our team from PKM Esa Unggul conducted an initial survey by visiting the Duri Kepa Village office to identify the needs and problems in the Duri Kepa area. After conducting the approach activity, a need was found at PAUD BKB Nusa Indah. In the second stage, our PKM team conducted a location survey at PAUD Nusa Indah to conduct interviews regarding the needs of PAUD Nusa Indah in the field of Design. The problems we found include: improving skills related to students' growth and development and creativity, and an increase in assets due to the limited space available to PAUD Nusa Indah, which means the preschool does not have much storage space for educational toys or similar items. The purpose of this PKM activity is to help increase creativity and comfort in classroom activities through the addition and improvement of supporting facilities for teaching and learning activities, with the aim of enhancing the skills, creativity, and learning enthusiasm of the students at PAUD Nusa Indah. The outputs of this PKM activity are: one scientific article published in an ISSN/ISBN journal, one article in print/electronic mass media, and a PKM activity video in the form of documentation that will be uploaded to YouTube. The goal of this type of economically unproductive partner output is expected to improve its quality and service.